Po prostu pyszne - Kalenuik, Ron. (Montreal : Tormont, 1993)
Polish translation of "Simply delicious Cooking". A complete simple recipe cook book.
Includes index.
Translation of: Simply delicious cooking.
Keywords: Cooking; Cuisine